Fajar Pers Muslim Bumi Putra di Masa Hindia Belanda: Wacana Anti Kapitalisme dalam Majalah Medan Moeslimin (1915-1926) - Triyanta, Agus (Panangkaran: Jurnal Penelitian Agama dan Masyarakat, 2023)
This study examines the Islamic Communist discourse in the Medan Moeslimin magazine in Surakarta in 1915-1926. This newspaper had created by Haji Misbah, an activist in Surakarta. This newspaper reviews many ideas such as Islamic discourse, movements and resistance that had initiated by Haji Misbach. In additionally, the idea of women's discourse had included in this newspaper. This newspaper often called out against the Dutch colonial government because it had felt to be oppressing the people. To facing toward the Dutch colonial government, Haji Misbach combined two different ideologies into one, namely the Islamic ideology and the Communist ideology. This had used to fight because these two ideologies were able to fight against the Dutch colonial government. This research is a literature review (Library Research) and this had used historical analysis methods including topic selection, heuristics, source criticism, interpretation and historiography. The primary sources is Medan Moeslimin newspaper and contemporary newspapers such as Islam Bergerak newspaper found in the Jakarta National Library. To support the data for research, the secondary books had used such as the Gerakan Komunis Islam in Surakarta in 1916-1942 and other books. This research had found the results: 1. The Medan Moeslimin newspaper was the media used by Haji Misbach to spread ideas against the Dutch colonial government; 2. This newspapers as media for Islamic da'wah in order to educate the people of Surakarta who still common in learning of Islam. [Penelitian ini mengulas wacana komunis Islam dalam majalah Medan Moeslimin di Surakarta tahun 1915-1926. Surat kabar ini didirikan oleh Haji Misbach seorang tokoh pergerakan di Surakarta. Surat kabar ini banyak mengulas berbagai gagasan seperti wacana keislaman, pergerakan dan perlawanan yang diserukan Haji Misbach. Surat kabar ini sering kali menyerukan penentangan terhadap pemerintahan kolonial Belanda yang menindas rakyat. Untuk menentang pemerintahan kolonial Belanda, Haji Misbach memadukan dua ideologi berbeda yaitu, Ideologi Islam dan Ideologi Komunis. Hal ini digunakan karena dua ideologi tersebut mampu melawan pemerintah kolonial Belanda. Ideologi Komunisme mengajarakan masyarakat tanpa kelas dan kesetaraan  sedangkan Ideologi Islam mengajarakan persatuan Islam persaudaran antar umat Islam maka dari itu Haji Misbah mengabung dua ideologi tersebut untuk melawan pemerinatah kolonial Belanda.  Penelitian ini menggunakan metode kajian pustaka (Library Research) dan menggunakan metode analisi historis meliputi pemilihan topik, heuristik, kritik sumber, interpertasi dan historiografi. Sumber primer yang digunakan berupa surat kabar Medan Moeslimin dan surat kabar sejaman seperti surat kabar Islam Bergerak   Untuk menunjang data penelitian penulis menggunakan buku-buku sekunder seperti Gerakan Komunis Islam di Surakarta tahun 1916-1942 dan buku lainnya. Penelitian ini  media yang digunakan Haji Misbach untuk menyebarkan gagasan menentang pemerintah kolonial Belanda, surat kabar Medan Moeslimin juga berperan sebagai media dakwah Islam di  Surakarta yang masih sangat awam dengan ajaran agama Islam.]